Experimental and theoretical insights into colossal supercapacitive performance of graphene quantum dots incorporated Ni3S2/CoS2/MoS2 electrode. (15th August 2023) - Sangabathula, Omkar; Kandasamy, Manikandan; Chakraborty, Brahmananda; Sharma, Chandra S.
Abstract: Transition metal sulfides (TMS) are promising electrode materials for supercapacitor applications due to their unmatchable advantages. To overcome the deficiency of individual metal sulfides, the combination of one or more pseudocapacitive transition metals with conductive carbon material can be a plausible solution. In this work, a simple and one-step hydrothermal synthesis method is used to fabricate the flower-like Ni3 S2 /CoS2 /MoS2 (NCMS) and Ni3 S2 /CoS2 /MoS2 -GQDs (NCMS-G) directly on Ni foam and used it as a binder-free electrode for high-performance supercapacitor applications. The NCMS-G-2.5 electrode possessed colossal specific capacitance (2364 Fg −1 at the current density of 2 Ag −1 ), excellent rate capability (55 % at the current density of 10 Ag −1 ), as well as good cycling stability (93 % retention after 10, 000 cycles at the current density of 20 Ag −1 ). Furthermore, assembled NCMS-G-2.5//rGO asymmetric supercapacitor (ASC) device delivered an excellent energy density of 84.8 Wh kg −1 and superior cycling performance (98 % capacitance retention after 10, 000 cycles). We have investigated the interactions between Ni3 S2 /CoS2 /MoS2 and carbon based nanostructure GQDs employing state-of-the-art Density Functional Theory (DFT) simulations. The interactions between Ni3 S2 /CoS2 /MoS2 and GQDs is not only long range van der Waals interactions, but also chemical interactions involving charge transfer from metal 3d orbital to C 2p orbital of GQDs are also present. Due to this synergic effect, there is enhancement in electronic states near Fermi level which may improve the conductivity of the hybrid structure. Enhanced quantum capacitance, improved conductivity and increased surface area for the hybrid structure may attribute towards superior charge storage performance for the hybrid structures which support experimental data. It is expected that the fabricated, unique, 3D flower NCMS-G-2.5 has potential prospects for developing advanced and high-performance energy storage devices. Graphical abstract: Unlabelled Image Highlights: A simple and one-step hydrothermal synthesis method is used to fabricate the flower-like NCMS-G electrode on Ni foam. A binder-free electrode fabricated for high-performance supercapacitor applications. Specific Capacitance of 2364 Fg −1 was delivered @ 2 Ag −1 and cyclic stability of 93% after 10000 cycles @ 20 Ag -1 . The interactions between Ni3 S2 /CoS2 /MoS2 and GQDs is investigated using Density Functional Theory simulations.